Computational fluid dynamics study of common stent models inside idealised curved coronary arteries. Issue 6 (26th April 2017) - Chen, Winson X.; Poon, Eric K. W.; Hutchins, Nicholas; Thondapu, Vikas; Barlis, Peter; Ooi, Andrew
Abstract: The haemodynamic behaviour of blood inside a coronary artery after stenting is greatly affected by individual stent features as well as complex geometrical properties of the artery including tortuosity and curvature. Regions at higher risk of restenosis, as measured by low wall shear stress (WSS < 0.5 Pa), have not yet been studied in detail in curved stented arteries. In this study, three-dimensional computational modelling and computational fluid dynamics methodologies were used to analyse the haemodynamic characteristics in curved stented arteries using several common stent models. Results in this study showed that stent strut thickness was one major factor influencing the distribution of WSS in curved arteries. Regions of low WSS were found behind struts, particularly those oriented at a large angle relative to the streamwise flow direction. These findings were similar to those obtained in studies of straight arteries. An uneven distribution of WSS at the inner and outer bends of curved arteries was observed where the WSS was lower at the inner bend. In this study, it was also shown that stents with a helical configuration generated an extra swirling component of the flow based on the helical direction; however, this extra swirl in the flow field did not cause significant changes on the distribution of WSS under the current setup.